Rapid effects of essential fatty acid deficiency on growth and development parameters and transcription of key fatty acid metabolism genes in juvenile barramundi (Lates calcarifer). Issue 11 (28th September 2015) - Salini, Michael J.; Turchini, Giovanni M.; Wade, Nicholas M.; Glencross, Brett D.
Abstract: Barramundi ( Lates calcarifer ), a catadromous teleost of significant and growing commercial importance, are reported to have limited fatty acid bioconversion capability and therefore require preformed long-chain PUFA (LC-PUFA) as dietary essential fatty acid (EFA). In this study, the response of juvenile barramundi (47·0 g/fish initial weight) fed isolipidic and isoenergetic diets with 8·2 % added oil was tested. The experimental test diets were either devoid of fish oil (FO), and thus with no n -3 LC-PUFA (FO FREE diet), or with a low inclusion of FO (FO LOW diet). These were compared against a control diet containing only FO (FO CTRL diet) as the added lipid source, over an 8-week period. Interim samples and measurements were taken fortnightly during the trial in order to define the aetiology of the onset and progression of EFA deficiency. After 2 weeks, the fish fed the FO FREE and FO LOW diets had significantly lower live-weights, and after 8 weeks significant differences were detected for all performance parameters. The fish fed the FO FREE diet also had a significantly higher incidence of external abnormalities. The transcription of several genes involved in fatty acid metabolism was affected after 2 weeks of feeding, showing a rapid nutritional regulation. This experiment documents the aetiology of the onset and the progression of EFA deficiency in juvenile barramundi and demonstrates that such deficiencies can be detected within 2 weeks in juvenile fish.